Articulación urbano - arquitectónica sostenible para la conectividad espacial, en el punto nodal de la antigua estación del ferrocarril, Palmira. (2022)
The railway line throughout Colombia has generated a rupture of the urban fabric in many of the municipalities due to demographic growth and the abandonment of railway transport, leaving as a result a discontinuity in the spaces that the railway line divides.